Perfil e teores de aminas bioativas e características físico-químicas em cervejas. - Bruno Goncalves Botelho (2009)
Profile and levels of bioactive amines and physico-chemical characteristics of beers. Spermidine, agmatine, putrescine and cadaverine were detected in 100% of the samples; tryptamine in 80% of the samples and histamine in 28% of the beer samples analyzed. Phenylethylamine was detected in only one sample whereas serotonine and spermidine were not found in any sample analyzed. Agmatine was the prevalent amine, with levels ranging from 7.0 to 22.0 mg/L; followed by putrescine (1.7 to 4.0 mg/L), cadaverine (0.2 to 0.9 mg/L), and spermidine (not detected to 0.7 mg/L). Tyramine was found in every sample at levels ranging from 0.5 to 2.3 mg/L, which are safe even forpatients under monoamine oxidase inhibitors. Every sample analyzed showed biogenic amines índex between 0.2 and 0.6, which indicates excelent microbiological quality of the samples analyzed. Regarding the physico-chemical characteristics of the beer samples, they were all in compliance with the Brazilian legislation, except for the Extra beer which did not reach the accepted values. Among physico-chemical parameters, the acidity and the pH correlated significantly with the amines, except with spermidine. There was significant correlation between amines and bitterness, what can be of relevance to the sensorial quality of the beer. Among the amines detected, putrescine, agmatine, cadaverine and tyramine correlated among them, indicating that they had thesame origin or are affected by the same factors.